SCAR marker linked to resistance gene of powdery mildew in bottle gourd [Lagenaria siceraria (Molina) Standl.] breeding line J083 - WANG Ling-ping; WU Xiao-hua; WANG Bao-gen; XU Pei; LI Guo-jing (浙江大学学报. 农业与生命科学版)
The genetic analysis of bottle gourd [Lagenaria siceraria (Molina) Standl.] resistance to powdery mildew was evaluated with a highly resistant breeding line J083 and a highly susceptible breeding line J73 and their F1, F2 populations. The results showed that the resistance to powdery mildew in J083 was controlled by a single recessive gene. From 100 amplified fragment length polymorphism (AFLP) primer pair combinations, a pair of stable polymorphic AFLP markers (E-ATG /M-CTC), 105 bp in size was obtained. The AFLP fragment was then converted to a sequence-characterized amplified region (SCAR) marker, named as GPDSATG/CTC75. This SCAR marker could be used effectively for molecular marker-assisted selection (MAS) in breeding programs to develop bottle gourd cultivars resistance to powdery mildew.